HLA sequencing identifies novel associations and suggests clinical relevance of DPB104:01 in ANCA-associated Granulomatosis with polyangiitis - Senapati, Sabyasachi; Singh, Harinder; BK, Thelma; Verma, Narendra; Kumar, Uma (Gene, 2024)
Granulomatosis with polyangiitis (GPA) is a rare systemic autoimmune disease. Major contributions of HLA genes have been reported; however, HLA typing-based diagnosis or risk prediction in GPA has not been established. We have performed a sequencing-based HLA genotyping in a north Indian GPA cohort and controls to identify clinically relevant novel associations. PR3-ANCA-positive 40 GPA patients and 40 healthy controls from north India were recruited for the study. Targeted sequencing of HLA-A,-B,-C,-DRB1,-DQB1, and -DPB1 was performed. Allelic and haplotypic associations were tested. Molecular docking of susceptibility HLA alleles with reported super-antigen epitopes was performed. The association of substituted amino acids located at the antigen-binding domain of HLA was evaluated. Genetic association of five HLA-alleles was identified in GPA. The novel association was identified for C*15:02 (p = 0.04; OR = 0.27(0.09-0.88)). The strongest association was observed for DPB1*04:01 (p < 0.0001; OR = 6.2(3.08-11.71)), previously reported in European studies. 35 of 40 GPA subjects had at least one DPB1*04:01 allele, and its significant risk was previously not reported from the Indian population. Significantly associated haplotypes DRB1*03:01-DQB1*02:01-DPB1*04:01 (p = 0.02; OR = 3.46(1.11-12.75)) and DRB1*07:01-DQB1*02:02-DPB1*04:01 (p = 0.04; OR = 3.35(0.95-14.84)) were the most frequent in GPA patients. Ranging from 89 % to 100 % of GPA patients with organ involvement can be explained by at least one DPB1*04:01 allele. A strong interaction between the HLA and three epitopes of the reported super antigen TSST-1 of Staphylococcus aureus was confirmed. Our study highlighted the potential applicability of HLA typing for screening and diagnosis of GPA. A large multi-centric study and genotype-phenotype correlation analysis among GPA patients will enable the establishment of HLA-typing based GPA diagnosis.